1994
DOI: 10.1128/mcb.14.9.6264
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces accumulation of p53 protein, but activation of a G1-phase checkpoint by low-oxygen conditions is independent of p53 status.

Abstract: function. In addition, cells expressing the human papillomavirus E6 gene, which show increased degradation of p53 by ubiquitination and fail to accumulate p53 in response to DNA-damaging agents, do increase their p53 levels following heat and hypoxia. These results suggest that hypoxia is an example of a "nongenotoxic" stress which induces p53 activity by a different pathway than DNA-damaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
334
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(357 citation statements)
references
References 73 publications
17
334
4
Order By: Relevance
“…In response to DNA damage, like ionizing irradiation (IR) (Kastan et al, 1991), ultraviolet (UV) irradiation (Maltzman and Czyzyk, 1984;Nelson and Kastan, 1994), hypoxia (Graeber et al, 1994), and ribonucleoside triphosphate depletion (Linke et al, 1996), p53 becomes activated as a transcription factor via speci®c post-translational modi®cations. The p53 protein is phosphorylated by a wide variety of protein kinases: in its transactivation domain by casein kinase (Ck) I, DNA-PK, ATM, JNK, and MAP kinases, and at its C terminus by cyclin dependent kinases (Cdks), PKC, and Ck II (see Martinez et al, 1997;Meek, 1994 and references herein).…”
Section: Cell Cycle Check Point Control and Apoptosismentioning
confidence: 99%
“…In response to DNA damage, like ionizing irradiation (IR) (Kastan et al, 1991), ultraviolet (UV) irradiation (Maltzman and Czyzyk, 1984;Nelson and Kastan, 1994), hypoxia (Graeber et al, 1994), and ribonucleoside triphosphate depletion (Linke et al, 1996), p53 becomes activated as a transcription factor via speci®c post-translational modi®cations. The p53 protein is phosphorylated by a wide variety of protein kinases: in its transactivation domain by casein kinase (Ck) I, DNA-PK, ATM, JNK, and MAP kinases, and at its C terminus by cyclin dependent kinases (Cdks), PKC, and Ck II (see Martinez et al, 1997;Meek, 1994 and references herein).…”
Section: Cell Cycle Check Point Control and Apoptosismentioning
confidence: 99%
“…Indeed Reed et al (1995) have suggested that wild-type p53 may sense DNA damage directly by increased binding to DNA with strand breaks, so that DNA damage itself may lead directly to stabilisation. However p53 is also induced by non-genotoxic stress such as hypoxia and heat shock (Graeber et al, 1994). In fact cells expressing E6 show increased degradation of p53 and cannot accumulate the protein even after DNA damage, but heat or hypoxia does induce accumulation in these cells (Kessis et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia or anoxia has been shown to induce p53 accumulation and apoptosis. 6,7 However, p53 activation by hypoxia does not appear to induce expression of classical p53 target genes such as p21, MDM2 and Bax, but can still mediate transrepression of certain genes such as a-tubulin. 8 This indicates that activation of p53 in response to hypoxia leads to a gene expression pattern that is different from that induced by p53 in response to g-irradiation, ultraviolet (UV) light and other DNA-damaging agents.…”
mentioning
confidence: 99%